The experience of motivation and adherence to group-based exercise of Norwegians aged 80 and more: a qualitative study - Irene Vestøl Stødle; Jonas Debesay; Zada Pajalic; Inger Marie Lid; Astrid Bergland (BMC, 2019)
Abstract Background Physical activity is crucial for public health; worldwide, across all age groups, exercise has been recognised as a factor that leads to improved health. However, many people do not engage in regular physical activity and hence miss the opportunity to achieve these significant physical and mental health benefits. With the benefits of exercise in mind, the aim of the present study is to describe the experiences of older people's motivation for participating in and adhering to a group-based exercise intervention in a local community setting. Methods A qualitative design was used in which semistructured interviews of three men and four women of an advanced age (81-92) were conducted; the participants described their experiences with their participation in and adherence to a long-term group exercise intervention programme in a community setting. Data were analysed using systematic text condensation and discussed in light of the salutogenetic theory. Results Four main themes emerged from the data collection: (1) Experience of health challenges: A meaningful starting point; (2) Adherence motivated by increased life-manageability; (3) Comprehensibility through skilled instruction and (4) Social and professional support enhancing motivation. The participants; who had experienced negative changes to their health and function, as well as to their life situation, chose to sign up for the exercise groups and continued to participate throughout the entire intervention. Attending group exercise sessions meant positive changes to physical, mental and social functions enhancing the participants' motivation to sustain their attendance and leading to positive behavioural changes that were important to their everyday lives. Conclusion Essential factors for these participants' decision to sign up for the exercise groups were the following: having important life areas connected to physical activity in their history and having belief in exercise as an effective way to restore function and coping; as well as having current experience of health challenges. Adherence to the group exercise was associated with better coping and the ability to fulfil roles and keep up with important life areas. Support from family, friends and professionals also contributed, both to the process of signing up, and adhering to this long-term intervention. The professionals' skills and the way the instructor tailored group instruction were emphasized as very important to the participants' adherence. Understanding of motivational factors for participation in and adherence to, exercise programmes is of great importance to older people, health professionals and society.